2020
DOI: 10.3892/ol.2020.12187
|View full text |Cite
|
Sign up to set email alerts
|

miR‑142‑5p promotes renal cell tumorigenesis by targeting TFAP2B

Abstract: The transcription factor AP-2 β ( TFAP2B ) serves an important role in kidney development. MicroRNAs (miRNAs) regulate carcinogenic pathways and have gained increasing attention owing to their association with human clear cell renal cell carcinoma (ccRCC) tumorigenesis. However, whether miRNAs could affect renal cell tumorigenesis by regulating TFAP2B expression has not been identified. The aim of this study was to investigate the effects of miRNA on TF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Other miRNAs targeted genes involved in cell–cell interaction, cell death, cell survival and cellular assembly and organization network including miR-142-5p, miR-151-3p, miR-218-1-3p, miR-335, and miR-340 related with AGO2, AGO3, CDH1, GABRA3 ( Figure 3 C). These results are similar to previous reports in renal cell carcinoma [ 34 ] and thyroid cancer [ 35 ]. The results of network analysis are presented in Figure 3 .…”
Section: Resultssupporting
confidence: 93%
“…Other miRNAs targeted genes involved in cell–cell interaction, cell death, cell survival and cellular assembly and organization network including miR-142-5p, miR-151-3p, miR-218-1-3p, miR-335, and miR-340 related with AGO2, AGO3, CDH1, GABRA3 ( Figure 3 C). These results are similar to previous reports in renal cell carcinoma [ 34 ] and thyroid cancer [ 35 ]. The results of network analysis are presented in Figure 3 .…”
Section: Resultssupporting
confidence: 93%
“…42 Over the years, there have been a growing body of studies that underscores the role of miR-142-5p in pathophysiological development of many diseases, such as epilepticus, 43 diabetic retinopathy, 44 nonalcoholic fatty liver disease, 45 and cancers. 46 Studies concerning the role of miR-142-5p in cardiovascular diseases is still lacking, but there is some evidence. Xu et al 47 found that miR-142-5p level is significantly increased in the atherosclerotic plaque obtained from ApoE −/− mice.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have highlighted the essential roles of TFAP2B, not only in the various tissues affected by the Char syndrome, but also in the neural processes, tumorigenesis, and craniofacial development (Fu et al, 2014; Fu et al, 2019; Hu & Bringmann, 2023; Ikram et al, 2016; Satoda et al, 2000; Zhu et al, 2020). Our lineage tracing has revealed that Tfap2b+ cells are progenitors for tooth development.…”
Section: Discussionmentioning
confidence: 99%